Influência de diferentes métodos de acabamento e polimento de preparos dentários na adesão de cimentos resinosos - Cardoso, Giovanni de Souza Goulart [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Neste estudo, o objetivo foi avaliar a eficácia de diferentes métodos de acabamento/polimento de preparo na resistência de união entre dente e cimento resinoso. Para isso, preparos de 0,5 mm foram feitos em 90 incisivos bovinos, e a superfície dentinária foi submetida a métodos de acabamento e polimento, divididos em grupos específicos. Posteriormente, a camada de smear foi analisada por microscopia eletrônica de varredura (MEV). Os dentes de cada grupo foram divididos em 3 subgrupos, de acordo com o tipo de procedimento adesivo: adesivo autocondicionante de 2 passos (GrupoSE), de 1 passo (GrupoUni) e adesivo convencional de 3 passos (GrupoTotal-Etch). Os corpos de prova foram posicionados em um dispositivo metálico, com o cimento resinoso dual Rely-X Ultimate (3M) aplicado, formando um cilindro que foi submetido a um teste de cisalhamento para avaliar a resistência da união. Os dados foram analisados estatisticamente com os testes ANOVA de dois fatores e o teste de Turkey, com nível de significância de 5%.

Objective: Evaluate the effectiveness of finishing and polishing methods on the bond strength between tooth and resin cement, aiming to improve the adhesive cementation technique. Material and Methods: Two hundred and forty bovine incisors were used. After extraction, the teeth were cleaned, the pulp chamber was accessed, and the dentin was exposed, with a standardized remaining dentin thickness of 0.8 mm. The teeth were embedded in acrylic resin and divided into eight groups, each subjected to different protocols of abrasion and finishing, using diamond burs and piezoelectric ultrasound. The surfaces were analyzed using scanning electron microscopy (SEM) to observe the Smear Layer and micromorphology. Bond strength was tested by microshear bonding, utilizing three adhesive techniques: self-etching, universal, and threestep etch-and-rinse. Statistical analysis was performed using ANOVA and Tukey's test, with a significance level of 0.05 Results: Topographical analysis revealed differences between the groups. Group 1 showed a smooth surface with a thin Smear Layer, while group 2 exhibited a more irregular surface with a thicker Smear Layer. The use of finer diamond tips (groups 4, 5, and 8) resulted in a more regular surface, with a more homogeneous Smear Layer. Conclusion: CVD diamond tips associated with piezoelectric ultrasound produce dentin surfaces with a Smear Layer conducive to adhesion, offering promising alternatives for durable adhesive restorations.
Influence of different finishing and polishing methods of dental preparations on the adhesion of resin cements
Keywords: Cimentos dentários; Dentin-bonding agents; Polimento dentário; Adesivos dentinários; Dental polishing; Dental cements